Are expansions cost effective for stock exchanges? A global perspective - Iftekhar Hasan; Markku Malkamäki (Bank of Finland, 2000)
This paper investigates the existence and extent of economies of scale and scope among stock exchanges.Evidence from 38 exchanges in 32 countries and 4 continents around the world for the years 1989-1998 indicates the existence of significant economies of scale and scope.The degree of such economies however differs by size of exchange and region.The largest stock exchanges show an increasing trend of cost effectiveness.Exchanges in North America and Europe report substantially larger economies of scale than those in the Asia-Pacific regions.
URN:NBN:fi:bof-20140807126
Keywords: 330; stock exchanges; mergers; regional alliances; economies of scale